2015
DOI: 10.18632/oncotarget.5873
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1 down-regulates proliferation and migration of breast cancer stem cells by inhibiting the Wnt/β-catenin pathway

Abstract: We investigated the miRNA profiles of breast cancer stem cells (CSCs) and non-CSC tumor cells by miRNA microarray and determined the effect of altered miR-1 expression on proliferation and migration of breast CSCs. The potential targets of miR-1 in the Wnt/β-catenin signaling were characterized by bioinformatics analysis and luciferase assay. We found that 14 miRNAs were up-regulated and 13 were down-regulated in the ESA+CD44+CD24−lineage− CSCs, related to ESA+CD44−CD24+lineage− non-CSC tumor cells. The miR-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 41 publications
2
44
0
1
Order By: Relevance
“…The Wnt/ β ‐catenin signaling pathway played a crucial role in promoting cell proliferation and migration , and previous studies revealed that HECT domain‐containing E3 ligases were implicated in down‐regulation of Wnt/ β ‐catenin signaling . As one member of the HECT domain‐containing E3 ligases family, we postulated that HACE1 might inhibit cell proliferation and migration through down‐regulation of the Wnt/ β ‐catenin signaling pathway.…”
Section: Resultsmentioning
confidence: 83%
“…The Wnt/ β ‐catenin signaling pathway played a crucial role in promoting cell proliferation and migration , and previous studies revealed that HECT domain‐containing E3 ligases were implicated in down‐regulation of Wnt/ β ‐catenin signaling . As one member of the HECT domain‐containing E3 ligases family, we postulated that HACE1 might inhibit cell proliferation and migration through down‐regulation of the Wnt/ β ‐catenin signaling pathway.…”
Section: Resultsmentioning
confidence: 83%
“…To further elucidate the molecular mechanism by which miR-150 regulates the proliferation of LSCs ( Figure 4A ), we tested the expression levels of genes including Notch2, Hsp90B1, and CTNNB1, besides Nanog (Zbinden et al, 2010; Liu et al, 2015; Zhu et al, 2015; White et al, 2016), which are known oncogenic and stem cell regulators that are implicated in leukemia initiation and progression. According to computational findings, they are targets of miR-150 ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, miRNAs have been shown to play an important role in the tumorigenesis of BC [2028], and in the control of BMP7 activation [2932]. However, previous studies on miR-137 never addressed BMP7 as a potential target [3337].…”
Section: Introductionmentioning
confidence: 99%